Filtering respiratory protective devices: what is the efficacy for fungal burden exposure? - Viegas, Carla (2019)
Background: Waste from non-biodegradable materials is sorted on waste sorting units to produce recyclable raw materials, leading to direct access to waste by workers. The organic residues present on waste serve as the substrate for numerous microorganisms, increasing workers' exposure to biological agents. The waste industry increases workers' exposure to microbial contaminants, such as fungi and bacteria (bioburden) and previous studies reported health risks associated with such environments. Filtering Respiratory Protective Devices (FRPD) is of mandatory use. Aspergillus spp. species are filamentous fungi commonly found in different environmental compartments, where they thrive as saprophytes. Some species among the Aspergillus genera can be occasionally harmful to humans. Only a few species are considered as significant opportunistic pathogens in humans. Aspergillus section Fumigati is an opportunistic pathogen of immunocompromised hosts and one of several Aspergillus species that cause a wide range of respiratory disorders. Another feature that should not be neglected is the fact of several Aspergillus sections have toxigenic potential leading to multiple occupational exposure risks. During protective equipment use, humidity and temperature conditions provide favorable conditions for fungal growth, among other microorganisms. The aim of this study was to characterize fungal distribution retained by FFRs. A case study developed in one waste management plant was developed to allow understanding the variables that influence FRPD contamination.